Characterization of fouling structure components and their relationships with associated macrofauna in three Northern Tyrrhenian port systems (Mediterranean Sea). (5th December 2022) - Tempesti, Jonathan; Langeneck, Joachim; Romani, Luigi; Garrido, Marie; Lardicci, Claudio; Maltagliati, Ferruccio; Castelli, Alberto
Abstract: Factors that promote the introduction and establishment of non-indigenous species (NIS) within port environments are not completely understood. In the present work the structure of fouling community was studied in three Northern Tyrrhenian port systems (Western Mediterranean), focusing on the relationships between fouling structure components and the associated macrofauna, considering whole communities and NIS assemblages. For each port system, fouling samples from two harbour types (large port and recreational marina) were collected and, within each large port, we considered two use destinations (commercial and touristic). Results showed that harbour type and use destination shaped the structure of sessile fouling differently, with their relative influence varying among port systems. Highly positive relationships were detected between macrofaunal sessile taxa and associated organisms for both whole communities and NIS assemblages. Possibly due to their complex three-dimensional morphology, erected bryozoans and serpulid tubes showed marked association with the majority of vagile taxa, especially NIS. These results suggest that high levels of spatial complexity of fouling basibionts could promote the invasion success within port environments. Graphical abstract: Image 1 Highlights: Fouling structure components were studied in Mediterranean port environments. A high spatial heterogeneity of fouling structure components was observed. Harbour type/use destination shapes fouling structure components assemblages. The complex physical structure of sessile organisms promotes NIS establishment.